THEME AND THEMATIC STRUCTURE IN RESORT GURU GURU VOL.6 BROCHURE - Putu Marlina Yanthi; Mirsa Umiyati (Program Studi Magister Ilmu Linguistik Universitas Warmadewa, 2018)
Every clause has its own character as a message which is known as thematic structure. Its elements are divided into theme and rheme. Therefore this research gives an overview about theme and its development in the text. The purpose of this study is to describe (1) the types of themes contained in the Resort Guru Guru vol.6 brochure and (2) how the form of the thematic progression is contained in Resort Guru Guru vol.6 brochure. This research data is obtained from the written text contained in a brochure namely Resort Guru Guru vol.6. Data were analyzed by using thematic theory by Halliday and Mathiessen and theory of theme development by Paltridge. Based on the analysis, there are two findings in the analysis of items contained in the brochure that is (1) the fillers of theme in the clause is divided by types of clause consisting of declarative, interrogative, and imperative clauses. (2) the theme development pattern contained in this brochure consists of constant theme, linear theme, and split rheme, and there is also another pattern that is the development between rheme to rheme and between rheme to theme and rheme.